Musicians’ pursuit of expertise-related goals is characterised by strategic regulation of functional and counterproductive affect - Breaden Madden, Gerard; Herff, Steffen A.; Beveridge, Scott; Jabusch, Hans-Christian (Frontiers in Psychology, 2024)
Background Emotion regulation is an important part of effective goal pursuit. Functional accounts of emotion regulation suggest that the attainment of challenging goals may be supported by regulating emotions which promote utilitarian over hedonic outcomes. When pursuing the challenging, long-term goal of acquiring expert musical skills and knowledge, musicians may wish to prioritise whichever emotions are most conducive to attaining this goal, even if those emotions are not necessarily positive. Methods Via an online questionnaire, musicians (N = 421) answered questions concerning their musical experience and their expertise-related practice goals. They also reported how strongly they experienced different emotions during practice, and how strongly they desired to either increase or decrease the intensity of those same emotions. Data were analysed using inferential frequentist statistics and Bayesian mixed effects models. Evidence ratios (ER) > 19 were considered strong evidence in favour of an effect. Results Our analysis showed that musicians experienced and desired strong levels of positive emotions in their practice. In addition, they reported greater desire to intensify positive compared to negative emotions [paired t (420) = 58.13, p < 0.001]. Our Bayesian mixed effects model provided strong evidence that greater desire to intensify anger increased the probability that an observation derived from a musician with stronger expertise-related goals [Est = 0.70; Odds (Est > 0) > 9,999]. In addition to anger, higher levels of expertise-related goals were increasingly predicted by less strong desire to intensify guilt and gloom and greater desire to reduce downheartedness (all ER > 19). Discussion Overall, musicians had a strong, general desire to intensify positive emotions during their musical practice. However, musicians with higher levels of expertise-related goals increasingly indicated a nuanced approach regarding how they desired to regulate certain negative emotions. Findings suggest that musicians engage in selective and sophisticated emotion regulation behaviour that aligns with their long-term commitment to develop musical expertise. They may prioritise emotions which may be functionally beneficial, whilst avoiding emotions which may be counterproductive or undermine efforts. Findings from this study contribute to our understanding of expertise-related, domain-specific emotion regulation behaviour and may inform the design of prioritised musical practice strategies.